Peter Piper's Practical Principles of Plain and Perfect Pronunciation - Anonymous (Salt Lake City, UT : Project Gutenberg, 2008)
"Peter Piper's Practical Principles of Plain and Perfect Pronunciation" by Anonymous is a playful guidebook written in the early 19th century. It aims to engage children and young learners with fun and whimsical examples to promote clear and accurate pronunciation in English. The book's lighthearted tone and entertaining content suggest it's designed primarily for educational purposes, focusing on enhancing speech and language skills. The book consists of a series of alliterative tongue twisters and riddles, each centered around a character or scenario that challenges the reader's ability to pronounce words correctly. These exercises serve not only as a means of improving pronunciation but also as delightful verbal puzzles. The writing features a rhythmic and playful style, as it encourages children to practice their articulation while enjoying the amusing adventures of characters like Peter Piper and others. Additionally, the book includes a hymn that reminds readers of the moral implications of their actions, enhancing its educational reach beyond language skills. (This is an automatically generated summary.)
Release date is 2008-04-09
Produced by Al Haines
Keywords: Alphabet books; Tongue twisters